226Health-related quality of life and all-cause mortality among older people: a prospective cohort study. (2nd September 2021) - Phyo, Aung Zaw Zaw; Ryan, Joanne; Gonzalez-Chica, David; McNeil, John; Woods, Robyn; Nelson, Mark; Murray, Anne; Lockery, Jessica; Gasevic, Danijela; Stocks, Nigel; Freak-Poli, Rosanne; ,
Abstract: Background: Health-related quality of life (HRQoL) is a measure of an individual's self-perceived health status. Few studies have examined HRQoL as a risk factor for mortality. This study examined whether HRQoL predicts all-cause mortality in older community-dwelling individuals from Australia and the United States enrolled in the Aspirin in Reducing Events in the Elderly (ASPREE) trial, and if this association varies across gender. Methods: The 19, 106 persons aged 65–98 years and free of known major life-limiting disease, who completed the 12-item short form (SF-12) HRQoL at ASPREE-baseline (2010–2014) were followed prospectively until 2017 for all-cause mortality. Cox proportional-hazard models were used to determine the association between the physical (PCS) and mental component scores (MCS) of HRQoL and all-cause mortality, adjusting for sociodemographic factors, health-related behaviours, and clinical measures. Results: There were 1, 052 deaths over a median 4.7-year of follow-up, with 11.9 events per 1, 000 person-years. A 10-unit increase in PCS was associated with a 17% decrease in all-cause mortality (95%CI: 0.77, 0.89). MCS was not associated with all-cause mortality. There was no evidence these associations were different between males and females (P-values for interaction: PCS 0.13 and MCS 0.44). Conclusions: PCS, but not MCS, was inversely associated with all-cause mortality in this large cohort of healthy older individuals. Key messages: Our findings support the decision of the Australian Commission on Safety and Quality in Health Care to incorporate the SF-12 into the routine collection of Patient Reported Outcome Measures as a policy goal for the Australian health system.